氣候變遷的安全與戰略意涵 - 林泰和; Tai-Ho, Lin (2011)
氣候變遷將成為國家未來數十年深遠的戰略挑戰，各國必須動用軍事力量處理暴風、乾旱、大批人口遷移和疫情散播的可能性遽增。氣候引起的危機可能讓部分政府垮台、助長恐怖主義勢力、動搖區域穩定。因此，學界必須嚴肅看待氣候變遷對國家安全與軍事戰略的含義。未來20年至30年，動盪地區，特別是撒哈拉沙漠以南、中東、南亞及東南亞，將面臨氣候變遷引發的糧食短缺、飲水危機，及災難性洪水，這可能迫使大國採取人道救援甚至軍事行動。由氣候變遷引起的自然災害，可能造成大量難民的遷徙，引發宗教衝突、傳染病散播，及基礎設施的嚴重破壞。氣候變遷將對各國軍事部門帶來巨大挑戰，因為許多重要的軍事設施，難逃海平面上升和暴風破壞的命運。\r美國國防部2010年2月向國會提交「四年期國防總檢討」（QDR），標示未來美軍建軍備戰思維，最重要的變化是首度納入氣候變遷可能衍生的安全問題，顯示氣候安全議題未來將左右美軍戰略及戰術規劃。氣候變遷將被視為「不穩定因素」，並將其列為導致戰爭的主要變數，未來安全威脅可能源自日益減少的世界資源和環境災難戰爭。氣候變遷也會對全球地緣政治產生衝擊。例如北極冰原快速消融，屆時將出現前所未有的「西北通道」，無論是爭奪航權，或是海底蘊藏的龐大天然資源，抑或搶佔此一區域戰略位置，環北極國家已紛紛採取行動。除此之外，氣候變遷對能源使用模式的影響，也是美軍必須立刻解決的問題。鑑於氣候變遷對國家安全的重要性，本文將嘗試探討氣候變遷對未來國家安全與戰略的意涵。 Climate change will be a far-reaching strategic challenge for states in the future. Countries would have to use military forces to deal with storms, drought, migration and spread of epidemic. Climate-induced crises may cause governments to collapse, contributing to terrorism and destabilizing global regions. In this sense, scholars must inquire the implications of climate change on national security and military strategy. In next 20 years to 30 years, unstable regions, particularly sub-Saharan Africa, the Middle East, South and Southeast Asia will face food shortages caused by climate change, water crisis, and catastrophic floods, which may force nation states to take military action for humanitarian assistance. Natural disasters caused by climate change may effect large scale migrations and refugees, causing religious conflicts, spread of infectious diseases, and serious damage to infrastructure. Climate change will bring great security challenges of national military departments, because many important military facilities would be vulnerable to rise of sea level and storm. In 2010 "Quadrennial Defense Review" (QDR), security problems derived from climate change are for the first time included in this report. Climate security issues would transform the future U.S. military strategy and tactical planning. Climate change will be regarded as "destabilizing factors", and the main variables that led to war. The future security threats may arise from the world's dwindling resources and environmental disaster. Climate change will have geopolitical impacts in global scale. For example, the rapid melting of Arctic ice would make the "Northwest Passage" real. Whether it is right to fight for navigation freedom, or the huge undersea natural resources, or to seize the strategic position in this region, Arctic states have already taken action. In addition, climate change will impact patterns of energy use, which also must be addressed by the U.S. military. In view of the importance of climate change on national security, this article will attempt to explore the implications of climate change on national security and military strategy in the future.